Microsatellite/SSR dataset: characterization of apple cultivars of the German Fruit Genebank - Lea Broschewitz; Stefanie Reim; Henryk Flachowsky; Monika Höfer (Scientific Data)
Abstract The German Fruit Genebank is a decentralized network focused on coordinating various germplasm collections across Germany to conserve and utilize the genetic resources of native fruit species. This aim emphasizes the necessity of trueness-to-type validation of genetic resources based on pomological and molecular characteristics. Between 2009 and 2021, multiple projects were undertaken to create an inventory of the apple (Malus ssp.) network of the German Fruit Genebank. Eight partner locations across Germany participated in these projects to assess the authenticity of apple cultivars. Firstly, at least two knowledgeable experts from the German Pomological Association characterized the apple accessions pomologically. Secondly, DNA fingerprint analysis was conducted for molecular characterization. The DNA fingerprint analysis employed a set of 17 simple sequence repeat markers and 8 reference genotypes recommended by the European Cooperative Programme for Plant Genetic Resources Malus/Pyrus working group and was carried out by ecogenics GmbH (c/o Microsynth AG, Balgach, Switzerland). 8,184 samples were analysed, resulting in the compilation of 1,404 molecular groups that correspond to distinct apple cultivars.